KESANTUNAN IMPERATIF TUTURAN GURU DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR 173 PEKANBARU - Erni, Sri Julia; Sinaga, Mangatur; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study discusses politeness imperative utterances of teachers in the learning process in primary schools 173 Pekanbaru based on the mode that is kind of imperative sentences. This study used a qualitative approach and descriptive method that aims to describe politeness imperative utterances of teachers in the learning process. This research subject a fifth grade teacher Sokolah base 173 Pekanbaru. This research uses verbal data type that originates in direct speech teacher while teaching. This study uses the technique of recording and record then classified based on the type of imperative sentence kesantunannya then analyzed based on the principle of modesty and scale kesantuanan then formulated into a knot. Based on the analysis of the data obtained the conclusion that the speech of the teacher based on types of sentences impertaif the imperative sentence request, invitation, ordinary, prohibitions, licensing. The sentence is not a lot of manners based on the principle of modesty and politeness scale.Key words: politeness imperative, imperative sentence, the teacher.